The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0142331218810085
|View full text |Cite
|
Sign up to set email alerts
|

An alumina rotary kiln monitoring system based on flame image processing

Abstract: In order to monitor the combustion condition and improve the product material quality, a digital image acquisition and processing method is adopted in alumina-sintering process. Two digital properties of flame grade and material grade are obtained by image data analyzing and smooth filtering, which provide reliable reference for operational optimization and automatic control of rotary kilns. This image acquisition system improves the operation of kiln effectively and reduces the working intensity and the manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Comparing with the allowable temperature range of MST (1055°C to 1250°C), the stable temperature of MST can ensure a high quailty of sintered alumina. In practical applications, some indirect indices were used to estimate the temperature in the burning zone of a rotary kiln such as use flame image method [26]. However, these indirect indices may cause some measurement errors due to the high temperature and heavy dusty environment along the rotary kiln.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing with the allowable temperature range of MST (1055°C to 1250°C), the stable temperature of MST can ensure a high quailty of sintered alumina. In practical applications, some indirect indices were used to estimate the temperature in the burning zone of a rotary kiln such as use flame image method [26]. However, these indirect indices may cause some measurement errors due to the high temperature and heavy dusty environment along the rotary kiln.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the range of MTI in a real operation of an IRAKP. Meanwhile, it is reported that MTI is majorly influenced by MST, kiln feed rate (KR), pressure at the kiln inlet (PI), RS, moisture content of the raw material (MR), FR, and AR [25][26][27].…”
Section: Data Classification and Data Rang Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Методика оценки состояния футеровки по данным, получаемым от тепловизоров, широко используется в промышленности [5][6][7].…”
Section: материалы и методыunclassified
“…Computer vision and image processing technology have been applied in many fields. Many scholars have applied machine vision to the flotation of nonferrous metal minerals and nonmetallic materials such as coal and silica sand (Fu and Aldrich, 2019; Lin et al, 2018; Massinaei et al, 2019; Popli et al, 2018; Vinnett and Alvarez-Silva, 2015; Xu et al, 2016). Some (Massinaei et al, 2019) applied computer vision technology to flotation columns in a coal preparation plant.…”
Section: Introductionmentioning
confidence: 99%